1990
DOI: 10.1016/0735-1097(90)90196-v
|View full text |Cite
|
Sign up to set email alerts
|

Afterload reduction with vasodilators and diuretics decreases mitral regurgitation during upright exercise in advanced heart failure

Abstract: In advanced heart failure, mitral regurgitation increases the burden of the failing ventricle and decreases effective stroke volume. Although tailored afterload reduction decreases mitral regurgitation at rest, it is not known if this benefit is maintained during upright exercise. Simultaneous radionuclide ventriculography and thermodilution stroke volumes were compared to measure the forward ejection fraction in 10 patients during upright bicycle exercise before and after therapy with vasodilators and diureti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(41 citation statements)
references
References 26 publications
1
36
0
1
Order By: Relevance
“…and mitral regurgitation, resulting in increased forward cardiac output. 4 Loop diuretics are routinely used as first-line agents to rapidly alleviate symptoms related to fluid overload. In the United States, loop diuretics were among the top 10% of the 200 most prescribed generic medications in 2008.…”
Section: Acute Pulmonary Edemamentioning
confidence: 99%
“…and mitral regurgitation, resulting in increased forward cardiac output. 4 Loop diuretics are routinely used as first-line agents to rapidly alleviate symptoms related to fluid overload. In the United States, loop diuretics were among the top 10% of the 200 most prescribed generic medications in 2008.…”
Section: Acute Pulmonary Edemamentioning
confidence: 99%
“…Nesta situação, ocorre dilatação do anel mitral e piora do grau de regurgitação mitral. Por outro lado, a dilatação ventricular também leva à distensão dos sarcômeros além da sua capacidade de gerar força eficientemente 82 . Estas duas observações levaram Stevenson e col a propor, nos últimos anos, mudanças marcantes na manejo de pacientes com IC avançada.…”
Section: Paradigmas Atuaisunclassified
“…Previous studies of tailored therapy and the recent ES-CAPE trial confirm that cardiac output improves as filling pressures are reduced. 12,18,22 The potential mechanisms described above may, however, have different impact than cardiac output increased by inotropic stimulation, which has consistently been associated with worse outcomes in previous experiences and in the ESCAPE population. The recent ESCAPE trial also confirms numerous previous studies regarding the prognostic importance of filling pressures, whereas cardiac output and index did not predict death or rehospitalization.…”
Section: Current Hemodynamic Goals For Chronic Heart Failure Do Not Imentioning
confidence: 99%
“…10 The ability of expert clinicians to estimate right atrial pressures from examination of the neck veins was reasonable but not perfect in the Evaluation Study of Congestive Heart Failure and Pulmonary Artery Catheter Effectiveness (ESCAPE) trial. 11 Right atrial pressures Ͼ10 mm Hg have been shown to track with pulmonary wedge pressures Ͼ22 mm Hg in Ϸ80% of patients with chronic heart failure, 12 although the prevalence of worsening right heart failure may be increasing with longer heart failure survival. Other qualitative indices that may be useful to expert examiners to reveal abnormally elevated filling pressures are the abdominaljugular reflex, 13 the Valsalva maneuver, 14 and prominent radiation of the pulmonic component of the second sound.…”
Section: Tailored To Signs As Well As Symptoms Of Congestionmentioning
confidence: 99%